VARK LEARNING STYLES TOWARDS ACADEMIC PERFORMANCE AMONG STUDENTS OF PRIVATE UNIVERSITY IN SELANGOR - Noor Nasyikin Md Zain; Fazilah Tamsir; Noor Ayuernie Ibrahim; Halimi Poniran; Amirul Syafiq Mohd Ghazali (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The objectives of this study are twofold: (a) to examine the influence of students’ learning styles on their academic performance; and (b) to identifies the preferred learning styles of students between high/low achievers, gender, and different clusters. By using VARK standard questionnaire, 433 undergraduate students from four faculties at the Private University in Selangor are used as observations for this study. The study finds that all students were unimodal learners and Kinesthetic (K) type of learning style is the learner type with the most number of students. High achievers are preferred Kinesthetic (K) learning style while Read/Write (R) learning style is more practiced by students with low achievement. Male students are more preferred Kinesthetic (K) learning style, but female students had a preference for Visual (V) learning style. Social science students are more preferred an Aural (A) as compared to the pure science students which are more preferred Read/Write (R) learning style. Further, this study confirms that Visual (V) and Kinesthetic (K) learning style preferences are positively and significantly influence students’ academic performance. This indicates that different subjects required different kinds of learning styles and instructions to optimally potentiate and benefit the students. This result is consistent with the “Meshing Hypothesis” which states that the learning outcomes could be highly achieved if learning was matched with a predominant learning style of the learner. This study gives a better representation of the current situation in the learning preferences among undergraduate students in Malaysia.